Adaptation and validation of the Arabic version of the COVID-19 anxiety scale - A. T., Alshomrani; El-Ashkar, Ayman M.; Aboregela, Adel M.; Alshahrani, Abdulaziz Nasser; Alhalafi, Abdullah Hassan (International Journal Of Community Medicine And Public Health, 2023)
Background: Marked dysfunctional psychological consequences of COVID-19 necessitate an invention of new tailored scales that can assess and monitor these manifestations. Coronavirus Anxiety Scale (CAS) is new reliable and validated scale constructed to measure COVID-19-related anxiety. Objectives were to make a well-structured CAS Arabic version and to assess its validity. Methods: Sousa and Rojjanasriratw scale adaptation guidelines were followed for CAS translation to Arabic language and a survey of sociodemographic data, CAS and validated COVID-19 fear scale Arabic-version distributed to cross-sectional university students’ sample. Internal consistency, factor analysis, average variable extracted composite reliability, Pearson correlation, and mean differences were calculated. Results: 233 students responded to the survey, and 44.6% were female. Cronbach’s alpha was 0.94, item-total correlations 0.891-0.905 and inter-item correlations 0.722-0.805. The factor analysis test showed one factor that explains 80.76% of the cumulative variances, average variance extracted 0.80 and composite reliability 0.95, and the two scales’ correlation r-value was 0.472. No significant difference between the scales regarding the score means when compared. The independent t-test showed no differences in means within each identified sociodemographic group. Conclusions: The translated Arabic version of CAS has high internal consistency reliability and convergent validity values, and factor analysis addressed unidimensional measures. So, the Arabic CAS version is a reliable and valid version that maintains the original English scale reliability and validity properties.